MODEL PENGELOLAAN JURNAL DALAM MENINGKATKAN KUALITAS ARTIKEL: Studi Pada Jurnal Pemberdayaan Masyarakat: Media Pemikiran Dan Dakwah Pembangunan - Aditya, Rahadiyand; Izudin, Ahmad (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2021)
This study aims to determine the strategy of the Journal of Community Development of Thought Media and Development Dawah in improving the quality of its articles. The research method in this article uses a qualitative descriptive approach with purposive sampling as a technique for withdrawing the informants. This research uses interviews and documentation studies in data collection. The results of this study are grouped into two parts, namely strategies to improve the ability of journal managers to operationalize OJS, and strategies to improve the quality of articles. Field findings show that training is carried out by bringing in experts, participating in training conducted by the Faculty Journal House and also the University Journal House, as well as several other similar trainings. The second group is the strategy to improve the final quality. There are three things, namely forming a team with clear job descriptions, giving rewards and punishments for the success of the achievements obtained by the journal. The last one is the participation of journal managers in training.